Accretion-modified Stars in Accretion Disks of Active Galactic Nuclei: The Low-luminosity Cases and an Application to Sgr A* - Jian-Min Wang; Jun-Rong Liu; Yan-Rong Li; Yu-Yang Songsheng; Ye-Fei Yuan; Luis C. Ho (The Astrophysical Journal Letters, 2023)
In this paper, we investigate the astrophysical processes of stellar-mass black holes (sMBHs) embedded in advection-dominated accretion flows (ADAFs) of supermassive black holes (SMBHs) in low-luminosity active galactic nuclei. The sMBH is undergoing Bondi accretion at a rate lower than the SMBH. Outflows from the sMBH-ADAF dynamically interact with their surroundings and form a cavity inside the SMBH-ADAF, thereby quenching the accretion onto the sMBH. Rejuvenation of the Bondi accretion is rapidly done by turbulence. These processes give rise to quasi-periodic episodes of sMBH activities and create flickerings from relativistic jets developed by the Blandford–Znajek mechanism if the sMBH is maximally rotating. Accumulating successive sMBH-outflows trigger a viscous instability of the SMBH-ADAF, leading to a flare following a series of flickerings. Recently, the similarity of near-infrared flare’s orbits has been found by GRAVITY/VLTI astrometric observations of Sgr A ^∗ : their loci during the last 4 yr consist of a ring in agreement with the well-determined SMBH mass. We apply the present model to Sgr A*, which shows quasi-periodic flickerings. An sMBH of ∼40 M _⊙ is preferred orbiting around the central SMBH of Sgr A* from fitting radio to X-ray continuum. Such an extreme mass ratio inspiraling provides an excellent laboratory for LISA/Taiji/Tianqin detection of mHz gravitational waves with strains of ∼10 ^−17 , as well as their polarization.